Genetic patterns of the corals Euphyllia glabrescens and Lobophyllia corymbosa across the Indonesian Archipelago - Jamaluddin Jompa; WIDYASTUTI UMAR; SYAFYUDDIN YUSUF; ASMI CITRA MALINA AR. TASSAKKA; Gino V. Limmon; RAHMI; AMANDA PRICELLA PUTRI; HALWI; HARTATI TAMTI; ABIGAIL MARY MOORE (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Jompa J, Umar W, Yusuf S, Tassakka ACM, Limmon GV, Rahmi, Putri AP, Halwi, Tamti H, Moore AM. 2020. Genetic patterns of the corals Euphyllia glabrescens and Lobophyllia corymbosa across the Indonesian Archipelago. Biodiversitas 21: xxxx. Scleractinian corals can reproduce in several ways, with two main sexual reproduction modes known as brooding and broadcast spawning. In this study, we described patterns of genetic variation within and connectivity between coral populations in western Indonesia (Seribu Archipelago), central Indonesia (Spermonde Archipelago), and eastern Indonesia (Ambon). We sampled two readily identifiable corals popular in the marine aquarium trade, one species widely reported as a brooder (Euphyllia glabrescens), the other as a broadcast spawner (Lobophyllia corymbosa). The mitochondrial COI genome was amplified for 117 samples. Within-population genetic variation was high, especially at the eastern Indonesia (Ambon) site. The genetic connectivity patterns were similar for the two corals, with high connectivity between the Seribu and Spermonde Archipelagos (despite a geographical separation of more than 1,000 km) and a lack of connectivity between these two sites and Ambon. These results indicate a potential barrier to gene flow between coral populations in western/central Indonesia and those to the east of Sulawesi Island.